A Line Loss Calculation Method Based on Big Data and Load Curve. Issue 4 (April 2021) - Yang, Yining; Xue, Yang
Abstract: In this paper, a new technique line loss calculation method based on load curve is presented. First, the data is preprocessed and the outliers are removed. Then the load curve is analyzed, and the load current per day is fitted by polynomial approximation method, and the load current curve is obtained by nine-order fitting. Considering that the current at different time points may affect the fitting of the data, time sequencing is carried out to improve the fitting accuracy. Then for the resistance calculation, the voltage difference between the platform side and the user side and the platform side current are used to calculate, avoiding the use of line length which is difficult to measure in practice. This method makes full use of the available power network data, rearranges it, calculates it according to the continuous load curve, and gets more accurate and reliable results.